2017
DOI: 10.4149/bll_2017_103
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disturbances induce malignant heart arrhythmias in rats

Abstract: OBJECTIVES: Metabolic disturbances are considered to condition the occurrence of malignant heart arrhythmias and negatively infl uence the chances of a patient to survive. To test this assumption, a model of metabolic syndrome was selected in which rats were receiving a diet resembling that of the westernized population. BACKGROUND: Metabolic syndrome is a comorbidity of major cardiovascular risk factors (dyslipidemia, hypertension, impaired glucose tolerance or insulin resistance, diabetes mellitus, and obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…To study myocardial susceptibility to dysrhythmias we used the ex vivo model of cardiac burst pacing for initiation and persistence of malignant re-entry dysrhythmias (Merrilat et al , 1990 ; Kihara & Morgan, 1991 ; Simor et al , 1997 ; Tribulová et al , 2002 ; Liptak et al , 2017 ). Using this model we demonstrated the decreased stimulating threshold and increased incidence of sustained ventricular dysrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study myocardial susceptibility to dysrhythmias we used the ex vivo model of cardiac burst pacing for initiation and persistence of malignant re-entry dysrhythmias (Merrilat et al , 1990 ; Kihara & Morgan, 1991 ; Simor et al , 1997 ; Tribulová et al , 2002 ; Liptak et al , 2017 ). Using this model we demonstrated the decreased stimulating threshold and increased incidence of sustained ventricular dysrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial susceptibility to persistent dysrhythmias was determined by induction of the 2 minute lasting sustained ventricular tachycardia (VT) or ventricular fibrillation (VF). Time to restore sinus rhythm by stop flow after sustained dysrhythmias was considered as the ability of myocardium to recovery electrical activity (Tribulova et al , 2002 ; Liptak et al , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, even a short period of HFD in gerbils can lead to radical inflammation and apoptosis causing cardiac remodeling (Sahraoui et al, 2016). Rats fed a high fat diet had an increased incidence of malignant ventricular tachyarrhythmias (Liptak et al, 2017) in the setting of induced ischemia. Furthermore, atria from rats fed high fat diet showed upregulation of transforming growth factor-β1 and matrix metalloproteinase-2 (atrial fibrosis pathway proteins), gap junction remodeling with alterations and distribution of connexin 40 (Cx40) and Cx43, broadened interstitial space, and myocyte disarray, and increased apoptotic cell death (Meng et al, 2017).…”
Section: Types Of Fat and Arrhythmia Developmentmentioning
confidence: 99%
“…Metabolic syndrome is an independent predictor of AF associated with the left atrial low voltage zone ( Dinov et al, 2014 ). Furthermore, MS is also associated with the increased risk of ventricular arrhythmia (VA) ( Fernández-Sada et al, 2017 ; Liptak et al, 2017 ) and was reported to contribute to a higher recurrence rate of outflow tract VA after catheter ablation ( Sardu et al, 2014 ). However, the underlying role of MS in the occurrence and development of such arrhythmia remains unclear.…”
Section: Translation In Modern Medicinementioning
confidence: 99%